The effect of technological progress on the emergence of social deviations interpreted through the issue of alienation and technology dependency - Luknar, Ivana (Sociološki pregled, 2025)
We accept technological innovation with great speed, focusing on their functional advantages, while social effects remain insufficiently interpreted. Modern technologies change modern society in an almost invisible, yet revolutionary manner, creating new social forms. This paper interprets social deviations, their transformation and emergence of new forms of social deviations due to the application of digital technology. The topic is justified by the method of content analysis of the published scientific material and conducted research, with the application of the multidisciplinary principle. The paper is a step forward in identifying and understanding specific forms of deviant behaviour in a new social context, which have emerged due to technological development. The paper is aimed at showing and analyzing the alienation phenomenon from the perspective of classical theoretical consideration in the current social context, as well as at providing the identification and understanding of various forms of technology dependency. The scientific importance of the article is reflected in its attempt to show negative social effects due to the excessive use of technology, as well as to point to the emergence of new forms of social deviation deriving from technological development, which did not even exist before the emergence of modern technology, and thus could not be the subject of consideration of classical theoretical interpretations. This article provides understanding and identification of the forms of social deviations emerging due to technological development, and also offers experts an opportunity to design preventive programs, thus reducing negative consequences for individuals and society in the long run.